Catalytic heterogeneous route for the synthesis of dimethyl isosorbide using dimethyl carbonate as methylating agent - Moreno-Tost, Ramón; Ginés-Molina, María José; Musolino, Manuele; Maireles-Torres, Pedro Jesús; Aricò, Fabio (My University, 2019)
In this contribution a heterogeneous catalytic route is envisaged by using as catalyst MgAlOx mixed oxides derived from hydrotalcite thermally treated (Mg/Al molar ratio of 3). The complete conversion of isosorbide is accomplished within the first hour but the DMI is not observed until 7 hours of reaction and its yield increases up to 100% after 24 hours of time on stream. The reutilization of the catalyst has shown a decline in DMI yield up to 52% after 4 runs even though the isosorbida conversion was of 100%.
Keywords: Isosorbide; Dimethyl carbonate; Dimethyl isosorbide